All‐Solution‐Processed, Ambient Method for ITO‐Free, Roll‐Coated Tandem Polymer Solar Cells using Solution‐Processed Metal Films. Issue 7 (1st July 2014) - Angmo, Dechan; Dam, Henrik F.; Andersen, Thomas R.; Zawacka, Natalia K.; Madsen, Morten V.; Stubager, Jørgen; Livi, Francesco; Gupta, Ritu; Helgesen, Martin; Carlé, Jon E.; Larsen‐Olsen, Thue T.; Kulkarni, Giridhar U.; et al.
Abstract A solution‐processed silver film is employed in the processing of top‐illuminated indium‐tin‐oxide (ITO)‐free polymer solar cells in single‐ and double‐junction (tandem) structures. The nontransparent silver film fully covers the substrate and serves as the bottom electrode whereas a PEDOT:PSS/Ag grid forms the semitransparent top electrode. All layers are roll‐coated/printed on a flexible substrate by using only two techniques: slot–die coating for up to 11 consecutive layers and flexo‐printing for the last Ag grid layer. The slot–die coated Ag film is compared to an evaporated Ag film in terms of surface morphological and topographical properties and to ITO in terms of flexibility. The slot–die coated Ag film demonstrates extremely low roughness (a root‐mean‐square roughness of 3 nm was measured over 240×320 μm2 area), is highly conductive (<1 Ω/□), highly flexible, and cost‐effective in comparison to other reported metal films applied in polymer solar cells. Such properties result in high fill factors exceeding 50 % in both single and tandem structures on large‐area devices (1 cm2) and the corresponding efficiencies exceed 2 %.